Chapter Sorption Detoxification as an Addition to Conventional Therapy of Acute Radiation Sickness and Iatrogenic Leukopenia - Sarnatskaya, V. V. (InTechOpen, 2019)
Leukopenia is an essential part of the clinical course of acute radiation sickness and is a side effect of anti-cancer treatment. In both situations, the main factors which determine the survival are the degree of bone marrow suppression and gastrointestinal tract damage due to the presence of a large pool of fast-dividing cells. Leuko- and neutropenia are main limiting factors which may contribute to chemotherapy failure. Hematopoietic cytokines the part of conventional therapy in this field, but their effects require boosting. That is why the use of means and methods of adsorption therapy is considered promising. Sorption therapy creates a basis for sorption detoxification, a doctrine of curative measures directed to the removal of toxic endogenous or exogenous compounds from body fluids. The most widely used types are the purification of blood or its components (hemosorption), oral administration of sorption materials (enterosorption) and application-sorption therapy of wounds and burns. In this chapter, the results of early and recent research and prospects for the use of carbon adsorption therapy for the treatment of acute radiation sickness and cytostatic myelosuppression are discussed.